NEGOTIATION OF PITY: THE DYNAMICS OF INDONESIAN MUSLIM IDENTITY IN CONTEMPORARY POPULAR CULTURE - Abdurrasyid Muhamad Rashid; Arsyad bin Abdurrahman; Marzuki Marzuki; Aida Fitriani (Yayasan Dinamika Literasi Jambi, 2026)
The development of popular culture within contemporary Muslim societies has generated new forms of religious expression that are increasingly intertwined with the creative industry and digital media. One prominent phenomenon is modest fashion, which is no longer confined to ethical or ritual religious functions but has evolved into a medium for representing identity, lifestyle, and visual piety. This article aims to analyze how modest fashion functions as an arena of negotiation between piety, Islamic identity, and the logic of popular culture within the context of Indonesian Muslim society. This study employs a literature-based approach by integrating perspectives from cultural studies and theories of the commodification of religion. The analysis draws on academic literature, media articles, and studies related to the Muslim fashion industry and religious practices in digital spaces, using discourse analysis as the primary analytical method. The findings indicate that modest fashion embodies an inherently ambivalent dynamic. On the one hand, it creates space for the articulation of an adaptive, reflective, and contextual Islamic identity, while simultaneously contributing to the economic and cultural empowerment of Muslim women. On the other hand, processes of commodification and mediatisation risk reducing piety to a visual and consumptive practice governed by market logic and digital popularity. Modest fashion, therefore, cannot be understood reductively either as a mere degradation of religious values or solely as a form of cultural progress. Rather, it constitutes a dialectical arena in which piety, identity, and consumption are continuously negotiated within the landscape of contemporary Muslim popular culture.